Prescribing Patterns of Antipsychotics in Schizophrenia Patients: A Study at Sikumana and Oesapa Primary Health Centers - Nesimnasi, Reinaldo Erasmus; Puspitasari, Hanni Prihhastuti; Yulistiani, Yulistiani (Faculty of Medicine Universitas Sebelas Maret, 2025)
Introduction: Schizophrenia is a chronic mental disorder with a rising prevalence, including in East Nusa Tenggara. Antipsychotics are the mainstay therapy, but prescribing patterns in primary care vary depending on patient condition and drug response. This study aimed to describe the prescribing patterns of antipsychotics among schizophrenia patients at Sikumana and Oesapa Primary Health Centers, Kupang City.Methods: A non-experimental descriptive design was applied using retrospective data from medical records of schizophrenia patients (ICD-X F20) during February–July 2025. Inclusion criteria consisted of patients who received antipsychotic therapy at both of two Primary Health Centers. Exclusion criteria included patients referred to higher-level facilities before receiving antipsychotic treatment.Results: A total of 42 patients with 129 visits were analyzed, dominated by males (52.4%) and the 25–44 age group (59.5%). Most were chronic patients (88.1%). Of 129 prescriptions, monotherapy predominated (57.4%), dominated by haloperidol (45 times) and risperidone (21 times). Combination therapy was also common (42.6%), particularly chlorpromazine + risperidone (29 times) and chlorpromazine + haloperidol (24 times). Trihexyphenidyl (103 times) was frequently prescribed as prophylaxis against extrapyramidal side effects, while diazepam (17 times) was used for anxiety or sleep disturbances. Several drugs were prescribed at lower doses than national and international guidelines, reflecting stable patient conditions in primary care, where lower doses remained effective while minimizing adverse effects.Conclusion: These findings highlight the dominance of typical antipsychotics and the limited variety of available drugs in primary care, underscoring the need for broader drug availability and more systematic monitoring of side effects.